An Update review on Childhood Interstitial Lung Diseases (chILD) (Bangladesh Medical Journal, 2024)
In recent times, we have encountered several cases of childhood Interstitial Lung Disease (chILD) in our clinical practice in Bangladesh. In developed world, there has been tremendous progress in the approach to chILD, with particular recognition that chILD in infants is often distinct from the forms that occur in older children and adults. Confirmation of diagnosis is challenging because of the rarity of ILD and the fact that the presenting symptoms of ILD often overlap those of common respiratory disorders. There are few case reports and almost no study on chILD in Bangladesh from net search. A growing part of the etiologic spectrum of chILD is being attributed to molecular defects. The pathogenesis of the various chILD is complex and the diseases share common features of inflammatory and fibrotic changes of the lung parenchyma that impair gas exchanges.  We are trying to diagnose chILD by excluding methods of suspected children in our aspects. However, in developed nations, clinical practice guidelines emphasize the role for high resolution computed tomography (HRCT) of chest, genetic testing, and lung biopsy in the diagnostic evaluation. Despite improvements in patient management, the therapeutic strategies are still relying mostly on corticosteroids although specific therapies are emerging. Larger longitudinal cohorts of patients are being gathered through ongoing international collaborations to improve disease knowledge and targeted therapies. Thus, it is expected that children with ILD will be able to reach the adulthood transition in a better condition.Bangladesh Med J. 2023 May; 52(2): 40-46